Refrigerated hydrocarbon fluids. Dynamic measurement. Requirements and guidelines for the calibration and installation of flowmeters used for liquefied natural gas (LNG) and other refrigerated hydrocarbon fluids. (12th February 2020) - British Standards Institution,
No abstract available